Hospitalization of newborns in Neonatal Unit: the meaning for the mother - Bibiana Sales Antunes; Cristiane Cardoso de Paula; Stela Maris de Mello Padoin; Tatiane Correa Trojahn; Andressa Peripolli Rodrigues; Caroline Sissy Tronco (Universidade Federal do Ceará, 2014)
This study aimed to understanding the meaning of hospitalization of the newborn child in the Neonatal Intensive Care Unit. It is a descriptive research of a qualitative approach. The interviews were conducted from December 2010 to April 2011, with seven mothers of newborns admitted to teaching hospital in the State of Rio Grande do Sul, Brazil. The content analysis resulted in three categories: the admission in the Neonatal Intensive Care Unit generates concerns and difficulties; need for professional care and use of technologies; in routine between home and the hospital the mother feels tired, sad and insecure. So, we must consider that there are characteristics of each mother in adapting to the Neonatal Intensive Care Unit environment. Attentive, responsive and individualized listening enable the professional care meets the needs of care to mothers in their uniqueness.